(untitled) (Práxis Educativa, 2017)
The objective of this study was to test the content and concurrent validity of Prolec-R (FIGUEIRA; LOPES, n.d., investigation version), exploring the relations as a proof of phonological awareness (phoneme synthesis), SICOLE-R evaluation (FIGUEIRA; LOBO; LOPES; JIMÉNEZ, n.d., investigation version). The theoretical background comprises the evaluation of cognitive processes involved in reading (JIMENEZ’S and CUETOS’S perspectives), in which the two tests employed assume too evaluate such processes, and are considered concurrent procedures. Both are destined to children from 6 to 12 years old. The methodology used, for exploration and accessibility, a sample containing children from the 2nd and 3rd year of elementary school, from the public and education systems in Coimbra and Beira Interior Norte. The results revealed the existence of a positive and significant relation between the reading of words, reading of pseudo words, grammatical structures, punctuation marks and sentence comprehension (PROLEC-R) and the phoneme synthesis (SICOLE-R). Keywords: Reading cognitive processes. Phonological awareness. Reading models.